2019
DOI: 10.1002/jnr.24569
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic in the adult deaf signing brain

Abstract: We have previously shown that deaf signers recruit partially different brain regions during simple arithmetic compared to a group of hearing non-signers, despite similar performance. Specifically, hearing individuals show more widespread activation in brain areas that have been related to the verbal system of numerical processing, i.e., the left angular and inferior frontal gyrus, whereas deaf individuals engaged brain areas that have been related to the quantity system of numerical processing, i.e., the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…These have shown to be solved through different procedures [ 41 ], rely on distinct brain networks [ 26 , 28 ] and modulate ERP components differently [ 23 , 25 ]. So far, one study investigated language modality and arithmetic processing using the fMRI [ 42 ]. Our study is unique as it is the first to investigate the impact of language modality on the time course of arithmetic processing.…”
Section: Discussionmentioning
confidence: 99%
“…These have shown to be solved through different procedures [ 41 ], rely on distinct brain networks [ 26 , 28 ] and modulate ERP components differently [ 23 , 25 ]. So far, one study investigated language modality and arithmetic processing using the fMRI [ 42 ]. Our study is unique as it is the first to investigate the impact of language modality on the time course of arithmetic processing.…”
Section: Discussionmentioning
confidence: 99%
“…While Andin et al (2019) failed to find behavioural group differences in reaction time and accuracy on their arithmetic task, they nevertheless highlighted differences in the neural networks deaf signers and hearing non-signers engage to calculate (but see Andin et al, 2022;Berteletti et al, 2022). Whereas language related brain regions in the left cerebral hemisphere are usually recruited for arithmetic fact retrieval (Dehaene et al, 2003), stronger activation of the right horizontal intraparietal sulcus was found in deaf signers compared to hearing non-signers.…”
Section: Discussionmentioning
confidence: 97%
“…It is finally worth mentioning that only single-digit operations were included in this study. This level of arithmetic reasoning might have not been sufficient enough to highlight group differences in adults ( Andin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical knowledge and ability play an important role in the successes of our social life (Ritchie and Bates, 2013), but most deaf individuals have some difficulty in acquisition of arithmetical skills even if they have the approximately same level of nonverbal intelligence as hearing peers (Braden, 1994;Moreno, 2000). Many studies have shown the close association between numerical magnitude processing and mathematical ability (LeFevre et al, 2010;De Smedt et al, 2013;Sasanguie et al, 2013;Fazio et al, 2014;Linsen et al, 2015), although few studies on the arithmetical abilities of deaf individuals (Masataka, 2006;Andin et al, 2014Andin et al, , 2020. It has been found in many studies that the poorer performance of deaf individuals in mathematics has generally been associated with their reduced language abilities (Kelly and Gaustad, 2007;Wu et al, 2013;Huber et al, 2014;Vitova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%